Analysis of General Purpose FPGA-based Development Boards Efficiency in DNA Processing Applications - SZÁSZ Csaba (Journal of Electrical and Electronics Engineering)
Deoxyribonucleic acid (DNA) sequence alignment represents one of the most expensive and computationally intensive tasks in bioinformatics. From hardware point of view the Field Programmable Gate Array (FPGA)-based accelerators looks the most adequate computing platforms to solve such complex applications. In recent years a plenty of FPGA accelerator platforms has been developed and presented in the related international literature. The main common goal of all these remarkable efforts is to drop the sequencing cost/genome ratio as much possible. Such solutions usually use specially developed FPGA-based hardware topologies and the cost of these systems has not been considered. This paper proposes a cheap and versatile solution that may bring closer the aim of personal genomics. For this purpose has been considered a ZyboZ7-10 general purpose development board available on the market at low price. This is a powerful FPGA-based ready-to-use hardware system. In laboratory conditions has been analyzed the efficiency of this board in gene sequence alignment. The experiments prove that by combining the advantages of widely accessible last generation-software technologies this board may be programmed to become a versatile and high speed genes alignment machine. A large set of test operations lead to the conclusion that is not absolutely necessary in all cases to design and implement expensive computing systems with specially designed hardware. Outstanding gene processing speeds also may be achieved with such general purpose boards. Therefore, the dream of personal genomics may be converted into reality even for a large scale of non-specialist users.